Prenatal psychosocial stress and children's sleep problems: Evidence from the ELSPAC-CZ study - Ksinan Jiskrova, Gabriela; Pikhart, Hynek; Bobák, Martin; Klanova, Jana; Stepanikova, Irena (Journal of sleep research, 2022)
Prenatal exposure to maternal stress may increase the risk of developing sleep problems in childhood. This study examined the association between prenatal stressful life events (PSLE) and children's sleep problems, taking into consideration their trajectory over time. Data were obtained from the Czech portion of the European Longitudinal Cohort Study of Pregnancy and Childhood (ELSPAC-CZ; N = 4,371 children). Mothers reported PSLE using an inventory of 42 life events and child sleep problems at five time-points (child age of 1.5, 3, 5, 7, and 11 years). The association was tested by a Poisson latent growth model, controlling for maternal and family demographics, birth characteristics, maternal depression, and alcohol use in pregnancy. The average rate of sleep problems was 2.06 (p < 0.001) at the age of 1.5 years and the rate of sleep problems decreased in a linear fashion over time (estimate = -0.118; p < 0.001). A higher number of PSLE was associated with a higher rate of sleep problems at the age of 1.5 years (incidence rate ratio [IRR] per interquartile range = 1.08, 95% confidence interval [CI] 1.05-1.12, p < 0.001) and with a reduced rate of decrease in sleep problems between the ages of 1.5 and 11 years (p < 0.001). Thus, PSLE were associated with chronicity of sleep problems in addition to their amount during early childhood. Prenatal exposure to stress may predispose individuals to the development of sleep problems in later life.
Keywords: prenatal stressful life events; spánek; latent growth modelling; Infant; Humans; Longitudinal Studies; zpožděný efekt prenatální expozice; Pregnancy; kojenec; dítě; Child; Female; lidé; Sleep Wake Disorders; Stress, Psychological; předškolní dítě; Sleep; ženské pohlaví; longitudinální studie; těhotenství; psychický stres; childhood sleep problems; poruchy spánku a bdění; Prenatal Exposure Delayed Effects; matky; Child, Preschool; Mothers